Investigation of a novel windcatcher with passive tube heat recovery - Liu, Miaomiao (2024)
Windcatchers are low-energy ventilation devices which can provide cooling and reduce buildings’ energy use. However, during unfavourable climate conditions, windcatcher operation could cause thermal discomfort and ventilation heat loss. Limited research has been conducted on pre-heating the supply air in windcatchers to address the issue and potentially increase their adoption in mild-cold climates. Therefore, this research proposes a novel windcatcher ventilation system integration with tube heat recovery (THR). By combining with a solid tube bank heat recovery device, the windcatcher can be operated under winter conditions to improve indoor ventilation while reducing buildings’ heating energy consumption. A three-dimensional computational fluid dynamics (CFD) model was developed to investigate the performance of the proposed windcatcher in ventilation rate, thermal comfort, and indoor air quality (IAQ). The CFD model was validated against the previous literature. The longitudinal pitch (LP) and the transverse pitch (TP) of the THR device were optimised based on the ventilation rate and tube thermal performance. The tube thermal performance can be improved by reducing LP and TP, increasing the fresh air supply temperature by up to 6.4 °C. Furthermore, the proposed windcatcher can provide sufficient ventilation for a typical classroom occupied by 15 people when the external wind speed exceeds 3 m/s. In addition, this project also explored the feasibility of the year-round operation of the windcatcher with tube heat recovery (THR) using the validated CFD model. The results showed that within the mild-cold months, the windcatcher with THR functioned as natural ventilation and improved the room temperature by an average of 3.1 °C. This extended the working period of the windcatcher throughout the year, especially during mild-cold months. During summertime, the highest indoor temperature observed in the space ventilated by the windcatcher with THR was 24.35 °C, which met the static overheating criteria. The windcatcher with THR reduced the ventilation heat loss by up to 8.1% in wintertime. It should be acknowledged that this windcatcher cannot provide satisfactory thermal comfort in months with outdoor temperatures below 9.41 °C, and more research should be done to improve the heat recovery efficiency. Furthermore, the CO2 concentration and spatial distribution in the ventilated space were investigated, which represent the IAQ. The effects of the occupant-influenced and external environment-influenced variables on the indoor CO2 levels were analysed. The results highlighted that occupant activity levels greatly affected CO2 levels in the ventilated space, with an increase of 44% from sedentary to medium working observed at the breathing heights based on the set conditions. For an occupancy density of 1.7-2.6 m2 /p in the classroom model, the indoor above outdoor CO2 levels were within 550 ppm at outdoor wind speeds above 3 m/s. The effect of heating/non-heating seasons on the indoor CO2 levels may be negligible for locations with high wind speeds all year round. Based on the UK’s year-round mean climate conditions, the CO2 level in the space ventilated by the windcatcher with THR was expected to reach Category I or II, according to EN 16798-1:2019.